Expressions and Meanings: A Phenomenological Approach to Semantics - LIELE MADZOU, Desmond Auffrey (Advances in Social Sciences Research Journal, 2022)
This article aims to analyze the relationship between ’’saying’’ and the ’’meaning of saying’’ under the banner of phenomenology. It is a question of resolving the conflict between the enunciation as the communicative background of an axiom and the content of knowledge as the intention of a thing. This is the problem of language and of the ontological description of the expressed object. This research tends to put back on the table of philosophy the claim of formal logic to want, wrongly, to claim to define the fundamental meanings by semantics. This research aims to posit saying as an expression referring to something. It reveals the uniqueness that naturally exists between saying and meaning in the noema-noesis relationship. Aware that all of life is language, this article sets out to establish the distinction between modes of reasoning and forms of reasoning in order to account for meanings as the meaning of saying. By scrutinizing the notion of judgment, it follows that significations as expressed meaning are phenomena.